2022
DOI: 10.3389/fmicb.2022.1012115
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 RNP-assisted validation of palmarumycin biosynthetic gene cluster in Lophiotrema sp. F6932

Abstract: Lophiotrema is a genus of ascomycetous fungi within the family Lophiotremataceae. Members of this genus have been isolated as endophytes from a wide range of host plants and also from plant debris within terrestrial and marine habitats, where they are thought to function as saprobes. Lophiotrema sp. F6932 was isolated from white mangrove (Avicennia officinalis) in Pulau Ubin Island, Singapore. Crude extracts from the fungus exhibited strong antibacterial activity, and bioassay-guided isolation and structure el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Fungi are an understudied resource for the discovery of novel natural products [ 4 , 11 , 16 , 18 , 49 , 50 , 51 ]. Marine fungi account for more than 60% of the 456 newly reported marine microbial natural products [ 52 ], an indication of the huge scale of untapped biosynthetic potential of naturally occurring fungi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungi are an understudied resource for the discovery of novel natural products [ 4 , 11 , 16 , 18 , 49 , 50 , 51 ]. Marine fungi account for more than 60% of the 456 newly reported marine microbial natural products [ 52 ], an indication of the huge scale of untapped biosynthetic potential of naturally occurring fungi.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of the genomic era followed by the exponential rise in availability of genomic data has led to the development of computational tools for genome mining capable of identifying biosynthetic gene clusters (BGCs) involved in the fungal secondary metabolism [ 12 , 13 , 14 ]. However, there is a noticeable disparity between the number of BGCs predicted by genome mining and the actual number of known compounds identified for any given microbial strain [ 15 , 16 , 17 , 18 ]. For instance, a study analyzing Penicillium genomes found 798 BGCs, but only 16% of the these could be connected to a pathway with a known product [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…F6932. 46 Palmarumycin C 8 showed inhibitory activity against S. aureus and A. fumigatus with the IC 90 values of 18 and 7 μg mL −1 , respectively.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 96%
“…Among the secondary barcode regions that have been used in fungal identification include two other nuclear ribosomal genes, i.e. 18S nuclear small subunit ribosomal DNA (nrSSU) and nuclear large subunit (nrLSU), and protein-coding loci such as the largest (RPB1) and second largest (RPB2) subunits of RNA polymerase II, beta-tubulin (tub2/BenA) and translation elongation factor 1-alpha (TEF1-α) (Dos Reis et al, 2022;Gakuubi et al, 2022b).…”
Section: 5: Identification Of Endophytic Fungimentioning
confidence: 99%
“…In MEA, the orange-red colour spread to the entire colony (Figure 5.9B). the wild-type strain after 21 days of growth in SDB, PDA and MEA media (Gakuubi et al, 2022b).…”
Section: 37: Morphological Characteristics Of Rnp-mediated Crispr-cas...mentioning
confidence: 99%